Orbital parameters and evolutionary status of the highly-peculiar binary system HD 66051 - Paunzen, E. (2018)
The spectroscopic binary system HD 66051 (V414 Pup) consists of a highlypeculiar CP3 (HgMn) star and an A-type component. It also shows out-of-eclipsevariability that is due to chemical spots. This combination allows thederivation of tight constraints for the testing of time-dependent diffusionmodels. We analysed radial velocity and photometric data using two differentmethods to determine astrophysical parameters and the orbit of the system.Appropriate isochrones were used to derive the age of the system. The orbitalsolution and the estimates from the isochrones are in excellent agreement withthe estimates from a prior spectroscopic study. The system is very close to thezero-age main sequence and younger than 120 Myr. HD 66051 is a most importantspectroscopic binary system that can be used to test the predictions of thediffusion theory explaining the peculiar surface abundances of CP3 stars.